Implementasi Sanksi Adat Nipassala dan Niwaluang dalam Pranata Sosial Masyarakat Hukum Adat Adolang: Perspektif Keadilan Restoratif dan Pluralisme Hukum - Sulastri Yasim; M. Chaerul Anwar (Jurnal Interpretasi Hukum, 2025)
Customary law constitutes a form of living law that continues to function effectively in regulating the social life of indigenous communities in Indonesia. Its operation is reflected in the enforcement of customary sanctions as mechanisms for social control and the restoration of communal balance. This study aims to analyze the implementation of Nipassalaand Niwaluang customary sanctions within the social structure of the Adolang indigenous community, as well as to examine the role of the Marrumbu Langi ritual as a mechanism for restoring social relations following violations of customary norms. This research employs an empirical legal method with a qualitative approach, utilizing participatory observation, in-depth interviews, and documentation of customary norms and practices. The findings indicate that Nipassala is imposed on customary authorities who violate customary obligations as a form of moral and institutional accountability, while Niwaluang applies to members of the indigenous community as a territorial separation from the customary domain due to violations of communal norms. Both sanctions are restorative rather than punitive, emphasizing social and spiritual rehabilitation. The Marrumbu Langi ritual functions as a reconciliation and social reintegration mechanism with binding legal implications within the customary system, particularly in restoring the legitimacy of customary leadership and maintaining social order. This study affirms that the Adolang customary sanction system embodies principles of communal restorative justice and underscores the continued relevance of customary law within Indonesia’s legal pluralism framework.